Blood‐based screening for bowel cancer may not resolve suboptimal screening participation in Australia. (15th May 2016) - Zajac, Ian T.; Duncan, Amy; Turnbull, Deborah; Wilson, Carlene; Flight, Ingrid
Abstract: Objective: Emerging blood‐based screening technologies for bowel cancer may improve screening participation compared to at‐home stool sampling. This study assessed the impact of different screening delivery scenarios with increasing health system interactions on sampling preferences and likelihood of screening participation. Methods: N=1, 561 persons aged 45 to 74 years completed a behavioural survey measuring demographics, readiness to screen, overall collection method preference, and proposed participation in stool and blood methods across four screening scenarios differing in terms of the number of required health system interactions. Results: Overall, respondents preferred a blood test (79.6%) compared to a stool test (20.4%). However, increasing health system interactions had a strong impact on the likelihood of participating in either sampling method ( p <0.001). Moreover, likelihood of participating in each of the four blood‐screening scenarios was significantly lower than the current at‐home stool sampling approach (all p <0.001). Conclusions: Blood‐based screening methods require increased contact with the health system but these interactions have negative impact on screening likelihood. All blood‐based scenarios showed lower screening likelihood ratings than the current at‐home FIT approach. Thus, blood‐based screening may not resolve suboptimal screening participation rates in Australia.